Geosciences and the Energy Transition - Nicholas J. Gardiner; Jennifer J. Roberts; Gareth Johnson; Daniel J. Smith; Clare E. Bond; Rob Knipe; Stuart Haszeldine; Sarah Gordon; Megan O’Donnell (Earth Science, Systems and Society)
A substantial and rapid decarbonisation of the global economy is required to limit anthropogenic climate change to well below 2°C average global heating by 2050. Yet, emissions from fossil fuel energy generation—which dominate global greenhouse gas emissions—are at an all-time high. Progress and action for an energy transition to net zero carbon is critical, and one in which geoscience sectors and geoscientists will play multiple roles. Here, we outline the landscape of the geosciences and the energy transition in the context of the climate crisis, and intergovernmental policies on climate and social justice. We show how geoscience sectors, skills, knowledge, data, and infrastructure, both directly and indirectly, will play a key role in the energy transition. This may be in the responsible sourcing of raw materials for low carbon energy technologies; in the decarbonisation of heating; and in the near-permanent geological capture and storage of carbon through novel technology development. A new and unprecedented challenge is to reach Geological Net Zero, where zero carbon emissions from geological resource production and consumption are achieved via permanent geological storage. We identify overarching and cross-cutting issues for a sustainable and fair net zero carbon energy transition, and the associated geoscience challenges and opportunities. Finally, we call for geoscience professionals to recognise and take responsibility for their role in ensuring a fair and sustainable energy transition at the pace and scale required.